Canada's and Mexico's trade position in the United States (U.S.) market - Kotsovos, D. (Statistics Canada OttawaCA, 1991)
Analyses for 1990, the value, distribution and nature of Canadian and Mexican merchandise exports to the U.S. with the aim of highlighting their competitiveness. Provides a broad overview of Canadian and Mexican exports to the U.S., and a detailed analysis of these exports by principal commodities.